Panel Discussion 1 | Investing in open infrastructure: The benefits and challenges in Japan - YAMAJI, Kazu (Institutional Knowledge at Singapore Management University, 2021)
Addressed some of the issues with tools in the research workflow and how to create a better scholarly communication environment. Covered the research infrastructure for open science at National Institute of Informatics and Japan through the use of OpenDOAR, LocalDOAR, arXiv and open source software.